Unravelling interspecific relationships among highland lizards: first phylogenetic hypothesis using total evidence of the Liolaemus montanus group (Iguania: Liolaemidae). Issue 1 (28th November 2019) - Abdala, Cristian Simón; Quinteros, Andrés Sebastián; Semhan, Romina Valeria; Bulacios Arroyo, Ana Lucia; Schulte, James; Paz, Marcos Maximiliano; Ruiz-Monachesi, Mario Ricardo; Laspiur, Alejandro; Aguilar-Kirigin, Alvaro Juan; Gutiérrez Poblete, Roberto; Valladares Faundez, Pablo; Valdés, Julián; et al.
Abstract: The South American lizard genus Liolaemus comprises > 260 species, of which > 60 are recognized as members of the Liolaemus montanus group, distributed throughout the Andes in central Peru, Bolivia, Chile and central Argentina. Despite its great morphological diversity and complex taxonomic history, a robust phylogenetic estimate is still lacking for this group. Here, we study the morphological and molecular diversity of the L. montanus group and present the most complete quantitative phylogenetic hypothesis for the group to date. Our phylogeny includes 103 terminal taxa, of which 91 are members of the L. montanus group (58 are assigned to available species and 33 are of uncertain taxonomic status). Our matrix includes 306 morphological and ecological characters and 3057 molecular characters. Morphological characters include 48 continuous and 258 discrete characters, of which 70% (216) are new to the literature. The molecular characters represent five mitochondrial markers. We performed three analyses: a morphology-only matrix, a molecular-only matrix and a matrix including both morphological and molecular characters (total evidence hypothesis). Our total evidence hypothesis recovered the L. montanus group as monophyletic and included ≥ 12 major clades, revealing an unexpectedly complex phylogeny.